Design of site plan of Kampung Edukasi Duren Sari to enhance educational potential and environment sustainability - Listyawan, Anto Budi; Pratama, Veri Mahendra; Subardi, Dewangga Saifullah Putra; Nafsah, Fauzan Luthfia; Triyono, Agus (Community Empowerment, 2025)
Kampung Edukasi Duren Sari, located in Kembangkuning Village, Cepogo District, Boyolali Regency, has very diverse educational tourism potential. Visitors are invited to enjoy tourism while refreshing their memories of ancient culture through Griya Kawruh and traditional children's games in Plataran Srawung. Tourists can also see firsthand the installation of renewable alternative energy at the Biogas House. However, the facilities and infrastructure in these locations are very limited and less attractive to tourists. The purpose of this activity is to revitalize the Kampung Edukasi through a site plan design to increase tourist attractiveness. Griya Kawruh is designed with a new landscape through the addition of a replica of a traditional well and tidying up the yard by installing paving blocks. The Plataran Srawung is equipped with replicas of stilt games and flower gardens, as well as a spectator stand. Meanwhile, the Biogas House is designed starting from arranging access to the location to comfortable seating for learning about biogas. The new site plan design is expected to transform traditional educational tourist spots into more elegant and attractive to visit.